The Influences of Lengthening Dimension of Ro-Ro Ferry Toward the Considerations of Hydrodynamics Characteristic and Loading Capacity Aspect - Andi Rachmianty; Suandar Baso; Syamsul Asri (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
The ferry business has become an important business segment for ship designers, builders and operators. Therefore, many ways have been done in order to increase ferry business through the proper design or converting ships by lengthening. This research is focused on the influences of lengthening a Ro-Ro ferry to hydrodynamics characteristic and loading capacity aspects. Moreover, the ships also are fixed in the same width and draft dimensions. The difference of the Ro-Ro ferries length is indicated by the addition of one column of car space where one column car space is given by car size including distance between car columns spaces which is an increment of every 5.88 meter. The total resistances of Ro-Ro ferries are obtained by ship model experiment in towing tank. There are 4 ship models that are made. The lengthening a Ro-Ro ferry is described into non-dimensional parameter by the ratio of ship length and displacement volume (L/V1/3). The hydrodynamics and the loading capacity of carried car aspects could be described into the ratio of resistance and loading capacity of carried car (RT/SUK) with ship speed. The research result shows that the lengthening of a Ro-Ro ferry affects on total resistance, speed, and loading capacity of carried car. The increase of total resistance is caused by higher residual resistance at high speeds and this is experienced by small length size. Therefore by lengthening the Ro-Ro ferry it could reduce total resistance in the same speed especially the residuary resistance but eventhough lengthening Ro-Ro ferry the effective speed should be considered. In additions, the effective speed for actual ships dimension in the same Rt/SUK 0.05 i.e. B5L10 is about 13.85 knot, B5L11 14.33 knot, B5L12 14.94 knot, and B5L13 15.45 knot respectively.